THE ROLE OF FUNCTIONAL STATUS ON THE RELATIONSHIP BETWEEN BLOOD PRESSURE AND COGNITIVE DECLINE. (16th November 2018) - Miller, L; Peralta, C; Fitzpatrick, A; Wu, C; Psaty, B; Newman, A
Abstract: The objective of this study was to examine whether self-reported functional status modified the association between blood pressure (BP) and cognitive decline among older adults. The study included 2, 097 U.S. adults aged 75 years and older from the Cardiovascular Health Study, followed for up to 6 years. Functional status was ascertained by self-reported limitation in activities of daily living (ADL; none vs. any). Cognitive function was assessed by the Modified Mini Mental State Exam (3MSE). We used linear mixed models to examine whether the presence of ≥ 1 ADL limitation modified the association between BP and cognitive decline. Potential confounders included demographics, physiologic measures, antihypertensive medication use and apolipoprotein E ɛ4 allele. We conducted stratified analyses for significant interactions between BP and ADL. The association between BP and change in 3MSE differed by baseline ADL limitation. Among participants without ADL limitation, elevated systolic BP (≥ 140 mmHg) was associated with a 0.16 decrease (95% CI: -0.25, -0.08); p-value for interaction<0.001, whereas in those with an ADL limitation, elevated systolic BP was independently associated with a 0.38 increase in 3MSE scores per year (95% CI: 0.13, 0.62). Elevated diastolic BP (≥80 mmHg) was associated with an increase in cognitive function in both groups, although the increase was greater in those with ADL limitation (0.52 points per year vs. 0.17 points per year, p-value for interaction =0.007). Elevated BP appears to be associated with decreases in cognitive scores among functioning older adults, and modest improvements in cognitive function among poorly functioning elders.